2012
DOI: 10.1371/journal.pone.0029493
|View full text |Cite
|
Sign up to set email alerts
|

Testing in Mice the Hypothesis That Melanin Is Protective in Malaria Infections

Abstract: Malaria has had the largest impact of any infectious disease on shaping the human genome, exerting enormous selective pressure on genes that improve survival in severe malaria infections. Modern humans originated in Africa and lost skin melanization as they migrated to temperate regions of the globe. Although it is well documented that loss of melanization improved cutaneous Vitamin D synthesis, melanin plays an evolutionary ancient role in insect immunity to malaria and in some instances melanin has been impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Earlier work showed that there was no effect of injection of vitamin D on P. berghei infection in mice (24, 25). Injection using the same protocol reported (25) offered no protection against ECM (Fig. S1A, B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier work showed that there was no effect of injection of vitamin D on P. berghei infection in mice (24, 25). Injection using the same protocol reported (25) offered no protection against ECM (Fig. S1A, B).…”
Section: Resultsmentioning
confidence: 99%
“…For injection, VD was dissolved in 100% ethanol and diluted to a working solution of 0.1 μg/ml in 0.02% Tween 80. Mice in the treatment group was injected with a 0.5 μg/kg every other day, starting three days before the PbA infection (25), while mice in the control group received equal volumes of 0.02% Tween 80. For oral administration, VD was dissolved in soybean oil before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6 mice were infected with PbA and monitored for peripheral blood parasitemia (31) and ECM clinical scores (25). DON (1.3 mg/kg) was administered i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were evaluated for the development of neurological signs associated with ECM and were given clinical scores between 0 (no signs) to 10 (moribund) using previously described criteria (25). Nearly all the untreated mice that were infected with PbA developed neurological signs by day 5p p.i.…”
Section: Don Treatmentmentioning
confidence: 99%